Can soy isoflavones in combination with soy protein change serum concentration of adiponectin and resistin? A systematic review and meta‐analysis on randomized clinical trials. Issue 12 (15th September 2022) - Hariri, Mitra; Amirkalali, Bahareh; Mollanoroozy, Ensiyeh; Gholami, Ali
Abstract: Some studies proposed the anti‐inflammatory effect of soy protein and soy isoflavones by changing the serum adiponectin and resistin levels. The purpose of this research was to determine the impact of soy isoflavones and soy protein on blood adiponectin and resistin levels in adults. Scopus, PubMed, Cochrane Library, ISI Web of Science, and ClinicalTrials.gov databases were searched until April 2022. The effect size was computed by the mean changes from the beginning for intervention and comparison groups and their standard deviation. In the case of significant heterogeneity, DerSimonian and Laird random‐effects model was used. Six and five clinical trials were selected for the systematic review and meta‐analysis, respectively. The overall estimate indicated that soy isoflavones in combination with soy protein did not significantly change serum adiponectin level (weighted mean differences (WMD) = 0.36 μg/ml; 95% confidence interval (CI): −0.26, 0.99; p  = .25), but significantly increased serum resistin level (WMD = 0.64 ng/ml, 95% CI: 0.25, 1.04; p  = .001). In combination with soy protein, soy isoflavones nonsignificantly increased serum adiponectin levels, but significantly increased resistin levels. New intervention studies with a high dose of soy isoflavones and soy protein in different parts of the world and an updated meta‐analysis are needed to confirm the results of our study. Abstract : Soy isoflavones in combination with soy protein non‐significantly increased serum adiponectin levels, but significantly increased resistin levels.